Silent Song - Marie-Louise Richards (Parse Journal, 2023)
This song is silent. It is written in many voices. Sourced from fugitivity existing on a lower frequency. Silently, it sings alongside inaudible tunes, tuning to, tuning with, knowing otherwise. Quiet search for materiality through the unseen and silent, as muted present absences. Learning to listen. This song is a survey of making spaces moving through and moving with affective frequencies. Silent rhythm, moving with, those who came before, dead or living, those with whom we are contemporary, those we conjure from our imagination—recovers collectivity as ways of coping, sensing, learning, thinking, resisting and imagining. Songs as ancestral inheritance. Citations reverberating through time and space. Its spatial potential generates and gathers. This song is the process of reading with (singing with), moving with (dancing with) black radical feminism and black thought. Citation as collective practice. Reconstructions. Weaving, between, past, present and future, means navigating differently, destabilising the notion of places as neutral, stable or fixed.